Arachne z ulotną nicią. Sygnatura kobieca w późnej poezji Bogusławy Latawiec - Dembińska-Pawelec, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The author of this sketch interprets Bogusława Latawiec’s poems in the context of women’s signatures. Poetry of Latawiec was usually read by critics in relation to the Polish avant-garde tradition represented by men: J. Przyboś and T. Karpowicz. The author recalls N. K. Miller’s proposition of feminist reading and her theory of text as an arachnology. Analysing Latawiec’s poems she shows some signs of feminine writing contained in metaphors: a thread, textiles, weaving, sewing, needlework. These signs are of particular importance in the metatextual poems talking about the process of creating as a weaving a text.